Pengaruh Investasi, Belanja Modal, dan Pendapatan Asli Daerah Pemerintah Daerah Terhadap Pertumbuhan Ekonomi - Zulvan, M Fahmi; Purbasari, Heppy (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
Economic growth is very important for the development of regencies and cities. The purpose of this study was to determine the effect of investment, capital expenditure, and local revenue (PAD) on economic growth. This study uses a population of district and city local governments in the Java and Bali regions, in the period 2018 to 2020. Furthermore, this study uses quantitative methods with data sources derived from the website of the Supreme Audit Agency (BPK) of the Republic of Indonesia and the Central Bureau of Statistics (BPS). The data used are in the form of district and city government financial reports and economic growth. Based on the sampling criteria, this study obtained 360 districts and cities from 2018 to 2020. This study uses multiple regression testing as a tool to answer the hypothesis and research model. The results of this study are that investment and PAD affect economic growth, which means that the amount of investment and PAD managed by local governments can cause economic growth in regencies and cities. Meanwhile, capital expenditure does not affect economic growth because regencies and cities that have high capital expenditure will reduce the value of economic growth.